Karakteristik guru BK millenial di Sekolah Menengah Atas Kota Palembang - Ahmad Rofi Suryahadikusumah; Kurniasari Kurniasari (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2019)
The majority of school counsellors in Palembang are millenial generations. Millennial is known as a dynamic and skilled generation in technology, but also feared the loyalty and commitment to work. Therefore, the research aims to illustrate the characteristics of a millennial school counselor in Palembang in a factual way. The research uses the survey method, to get an accurate and clear picture of the different aspects of the millennial school counselor in Palembang. Results found that 1) Personally, the school counselor is able to keep up with changes and are accustomed to improving professionalism, 2) socially involved in school activities, but lack of external collaboration, and difficult to understand the conditions of students, and 3 ) capable of technology, but low in innovating. Research implicates the development of theory and practice of management and supervision of guidance and counseling and the development of the profession Counselor in the 4.0 era